Feasibility of applying real-time optical imaging during bronchoscopic interventions for central airway obstruction - Williamson, J.; McLaughlin, R.; Phillips, M.; Curatolo, A.; Armstrong, J.; Maddison, K.; Sheehan, R.; Sampson, D.; Hillman, D.; Eastwood, Peter (2010)
Interventional bronchoscopists manage central airway obstruction (CAO) through dilation, tumor ablation, and/or stent insertion. Anatomical optical coherence tomography (aOCT), a validated light-based imaging technique, has the unique capacity of providing bronchoscopists with intraprocedural central airway measurements. This study aims to describe the potential role of real-time aOCT in guiding interventions during CAO procedures. Methods: Prospective case series were recruited from patients referred for bronchoscopic management of symptomatic CAO. Preprocedure chest computed tomography (CT) scans were analyzed for relevant airway dimensions, such as stenosis caliber and length, and aided procedure planning. During bronchoscopy, an aOCT fiberoptic probe was inserted through the working channel of the bronchoscope to image the airway stenosis. From these aOCT images, stenosis dimensions were measured and compared with the preprocedure CT measurements. Preprocedure and postprocedure spirometry, Medical Research Council dyspnea score, and Eastern Cooperative Oncology Group performance status were collected to assess intervention efficacy. Results: Fourteen patients were studied. CT and aOCT-based measurements of airway caliber and length correlated closely (r 2=0.87, P < 0.001). Bland-Altman analysis showed strong agreement between measurements (mean difference 0.4 ± 8.6 mm). The real-time nature of aOCT imaging provided the advantage of more up-to-date measurements where a delay occurred between CT and bronchoscopy or where the quality of the CT image was suboptimal. After bronchoscopy, the predicted forced expiratory flow in 1 second increased from 67 ± 26% to 78 ± 19% (P = 0.04). Eastern Cooperative Oncology Group and dyspnea scores improved in 83% and 75% of the patients, respectively. Conclusions: aOCT provides real-time measurements of obstructing central airway lesions that can assist therapeutic interventions such as selection of endobronchial stents and airway dilatation procedures. Copyright © 2010 by Lippincott Williams & Wilkins.